Effect of trunk-restraint training on function and compensatory trunk, shoulder and elbow patterns during post-stroke reach: a systematic review. (25th June 2014) - Pain, Liza M.; Baker, Ross; Richardson, Denyse; Agur, Anne M. R.
Abstract: Purpose : The purpose of this systematic review was to determine the effect of trunk restraint (TR) training on post-stroke compensatory trunk movements during functional reach, and to identify functional gains of TR within the context of the International Classification of Functioning, Disability and Health (ICF). Methods : Six databases were searched prior to 20 February 2013. Randomized control trials (RCTs) comparing the effects of a post-stroke reaching intervention with and without TR in the adult post-stroke population were included in this review. Data related to study inclusion/exclusion criteria, methodology, study participants and between-group outcomes ( p < 0.05) were extracted. All outcomes were categorized according to functional domains defined within the ICF. Results : Five RCTs met the inclusion criteria. TR groups demonstrated significant between-group differences ( p < 0.05) for decreased compensatory trunk displacement (4/5 RCTs), increased elbow extension (3/5 RCTs) and increased shoulder flexion (2/5 RCTs). All significant between-group differences fell within the Body Structure/Function domain of the ICF. Conclusions : Trunk restraint is a simple, cost-effective technique that may help to reduce compensatory trunk/shoulder/elbow movements in the post-stroke adult population. Synthesis of study outcomes also highlights applications of TR to clinical practice and areas for further research. Implications for Rehabilitation: The ability to use the shoulder and elbow to perform functional reach is a primary goal in post-stroke recovery; however, compensatory trunk movements are often used to achieve the reaching goal. Long-term use of compensatory strategies may contribute to secondary impairments, such as learned non-use, joint contractures and pain. Trunk restraint enables functional reach practice, while limiting compensatory strategies in the moderately to severely impaired stroke population.